2022
DOI: 10.1177/13524585221139575
|View full text |Cite
|
Sign up to set email alerts
|

Selective vulnerability of brainstem and cervical spinal cord regions in people with non-progressive multiple sclerosis of Black or African American and European ancestry

Abstract: Background: We evaluated imaging features suggestive of neurodegeneration within the brainstem and upper cervical spinal cord (UCSC) in non-progressive multiple sclerosis (MS). Methods: Standardized 3-Tesla three-dimensional brain magnetic resonance imaging (MRI) studies were prospectively acquired. Rates of change in volume, surface texture, curvature were quantified at the pons and medulla-UCSC. Whole and regional brain volumes and T2-weighted lesion volumes were also quantified. Independent regression model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
0
2
0
1
Order By: Relevance
“…One of these studies found that African American pwMS had greater total spinal cord atrophy, and more specifically, also within the ventral and dorsal regions, compared to White pwMS (39). The other study demonstrated that Europeans with MS had greater volume loss at the medulla-upper cervical spinal cord region than African Americans, but that African Americans had greater baseline pontine volume loss, which continued to worsen at one-year follow-up (41).…”
Section: Studies Looking At Atrophymentioning
confidence: 99%
“…One of these studies found that African American pwMS had greater total spinal cord atrophy, and more specifically, also within the ventral and dorsal regions, compared to White pwMS (39). The other study demonstrated that Europeans with MS had greater volume loss at the medulla-upper cervical spinal cord region than African Americans, but that African Americans had greater baseline pontine volume loss, which continued to worsen at one-year follow-up (41).…”
Section: Studies Looking At Atrophymentioning
confidence: 99%
“…Auch die okuläre Dysmotilität, einschließlich der internukleären Ophthalmoplegie (INO) und der bilateralen INO mit dem Schielauge, ist bei MS weit verbreitet [77]. Es gibt nur wenige Artikel in der Literatur, die sich mit den ethnischen und rassischen Unterschieden bei diesen Befunden befassen, was erwähnenswert ist, zumal es Literaturstellen gibt, die darauf hindeuten, dass die Hirnstammregionen, die diese Funktionen steuern, bei Menschen mit afroamerikanischer Abstammung strukturell besonders anfällig sind [78]. Zu diesem Thema sind weitere Studien erforderlich.…”
Section: Okuläre Dysmotilitätunclassified
“…Similarly, ocular dysmotility, including internuclear ophthalmoplegia (INO) and wall-eyed bilateral INO, are highly prevalent in MS. 77 There is a dearth of literature examining ethnic and racial disparities in these findings, which is worth mentioning, particularly as there is literature suggesting that structurally the brainstem regions controlling these functions are selectively vulnerable in those with African-American ancestry. 78 Further study is needed on this topic.…”
Section: Bodymentioning
confidence: 99%